Peta Isolat Bakteri Dan Sensitifitasnya Pada Penderita Gangren Diabetik Di Rumah Sakit Angkatan Laut Dr. Ramelan Surabaya - NI LUH AYU MADE INTAN EDYASSARI PUTRI UTAMI (Universitas Hang Tuah, 2018)
Abstract Background: Diabetic gangrene is one of the complications of Diabetes Mellitus (DM) characterized by open wounds on the skin surface to the dermis layer. One of the complicating factors of the wound healing process is the infection of germs. Infection therapy in diabetic gangrene often associated with the use of antibiotics. The purpose of this study was to determine the germs that found in diabetic gangrene and its sensitifity to antibiotic in diabetic gangrene patients at Naval Hospital Dr. Ramelan Surabaya. Methods: This study is a retrospective descriptive study using 60 data samples that have fulfilled the inclusion criteria and obtained from the result of pus culture in diabetic gangrene at the Clinical Pathology Laboratory of Naval Hospital Dr. Ramelan Surabaya. Results: The results obtained from this study indicate the presence of 13 types of germs found in pus culture of diabetic gangrene patients and the most common found were Escherichia coli (33,3%). While the results on the sensitifity test showed that antibiotics with the highest sensitifity were Cefoperazone/ Sulbactam, Meropenem, and Levofloxacin (92.3%), whereas the lowest sensitifity antibiotic was Ampicilin (15.3%). Conclusion: Diabetic gangrene is often followed by the occurrence of infections that can be caused by various germs, and each germ has a different sensitifity to antibiotics. The culture of gangrene must be done because it is used to determine the type of antibiotic used for the treatment of diabetic gangrene based on the type of germs that infects. However, Cefoperazone/ Sulbactam, Meropenem, and Levofloxacin antibiotics may be the primary antibiotic choice because they have a high level of sensitifity